High-performance and moisture-resistant red-emitting Cs2SiF6:Mn4+ for high-brightness LED backlighting. Issue 8 (7th February 2019) - Liu, Yong; Zhou, Zhi; Huang, Lin; Brik, Mikhail G.; Si, Shuaichen; Lin, Litian; Xuan, Tongtong; Liang, Hongbin; Qiu, Jianbei; Wang, Jing
Abstract : Narrow-band Cs2 SiF6 :Mn 4+ phosphors with high external quantum efficiency were synthesized by a low-temperature co-precipitation approach. Moreover, the water-resistance stability of the phosphors was significantly improved by a facile surface passivation strategy. Abstract : Narrow-band red-emitting fluoride phosphors for wide color gamut LED backlights have evoked considerable attention, due to their fascinating optical properties. Unfortunately, poor moisture resistance often restricts their further applications in optoelectronics. Herein we developed a Cs2 SiF6 :Mn 4+ red phosphor using a low-temperature co-precipitation method and passivating it by using H2 O2 . The phosphor shows a very high external quantum efficiency (EQE) of ∼85% and exhibits excellent moisture stability retaining 74% of its emission intensity after being exposed to high temperature (85 °C) and high humidity (85%) (HTHH) for 168 h. Finally, the high brightness white LED devices combined with the passivated Cs2 SiF6 :Mn 4+ exhibit high luminous efficacy of 133 lm W −1 and wide color gamut (∼84.7% NTSC). The results demonstrate that the passivated Cs2 SiF6 :Mn 4+ with high EQE and excellent moisture-resistance is promising as a narrow-band red emitting phosphor for wide color gamut LED backlights.